Essential Mathematical Biology
Essential Mathematical Biology is a self-contained introduction to the fast-growing field of mathematical biology. Written for students with a mathematical background, it sets the subject in its historical context and then guides the reader towards questions of current research interest, providing a comprehensive overview of the field and a solid foundation for interdisciplincary research in the biological sciences. Topics cover include: Population dynmaics, Infectious diseases, Population genetics and evolution, Dispersal, Molecular and cellular biology, Pattern formation, Cancer modelling.